Festkörperphysik - Gross, Rudolf (De Gruyter Studium, 2022)
For years, this textbook has been held in high esteem for conveying information in a pedagogically challenging and modern way. The authors do not just present the full spectrum of solid-state physics but also provide an easily comprehensible, structured introduction to further special topics. Alongside an additional chapter on antiferromagnetic resonance, the topics superconductivity and topological quantum materials have been fully updated.